A Study of Dental Students Attitudes toward the Educational Environment of Kerman University of Medical Sciences Iran Using the Dundee Ready Education Environment Measure - Mahsa Kalantary; Mahsa Sayadi; Maryam Sadat Hashemipoor (Kerman University of Medical Sciences, 2016)
Background & Objective: Educational institutes have different approaches to the evaluation of their activities Many factors in the teaching process affect the learning process This study investigated the attitudes of dental students in the School of Dentistry of Kerman University of Medical Sciences (Iran) toward the current educational condition and learning atmosphere using the Dundee Ready Educational Environment Measure (DREEM) Methods: This descriptive crosssectional study was performed on 205 dental students in 2013 DREEM includes questions on demographic information and 50 questions in 5 subscales (students perceptions of learning students perceptions of teachers students academic selfperceptions students perceptions of atmosphere and students social selfperceptions) The collected data were then analyzed using SPSS software Results: The mean of the achieved scores in the 5 subscales was 15223 ± 1563 out of 250 among men and 16464 ± 1880 among women Amongst the study population 9% found the educational conditions highly undesirable Statistically significant differences were observed only for the learning subscale between the 3rdyear and 4thyear students Conclusion: Students attitudes toward the learning environment of Kerman University of Medical Sciences were mostly positive but there were some inconsistencies It seems that stress fatigue and lack of feedback from teachers has caused negative emotions among students